Mr. Ritter on Monetary and Fiscal Policy - Turvey, Ralph (Review of Economic Studies, 1956)
Journal Article Mr. Ritter on Monetary and Fiscal Policy Get access Ralph Turvey Ralph Turvey London Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 24, Issue 1, 1956, Pages 71–72, https://doi.org/10.2307/2296240 Published: 01 July 1956